Potential application for antimicrobial and antileukemic therapy of a flavonoid-rich fraction of Camellia sinensis - de Souza, Mariana C.; de Souza Mesquita, Leonardo M.; Pena, Fabíola L.; Tamborlin, Leticia [UNESP]; da Silva, Laise C.; Viganó, Juliane; Antunes, Adriane E. Costa; Luchessi, Augusto D. [UNESP]; Duarte, Marta C. Teixeira; Barbero, Gerardo F.; Rostagno, Mauricio A. (Elsevier, 2022)
The antimicrobial and antileukemic effect of a purified fraction of flavonoids from the leaves of Camellia sinensis was evaluated. An extraction yield of 9.77 mg.g-1 total flavonoids was recovered through a pressurized liquid extraction associated with solid-phase extraction. This fraction was tested against pathogenic microorganisms (Staphylococcus, Salmonella, and Enterococcus), considering the minimum inhibitory concentration. In addition, the human monocyte cell line THP-1, derived from a patient with acute monocytic leukemia, was used for the antitumor assay. The results show that the flavonoid-rich fraction obtained by coupling a Pressurized Liquids Extraction in-line with a Solid Phase Extraction (PLE-SPE) has a high antimicrobial effect and resulted in cell cycle blockage G0 / G1, increased DNA fragmentation, and altered leukemic cell morphology. These results suggest that a flavonoid-rich fraction obtained from Camellia sinensis can be applied as potential adjuvants in chemotherapy treatment to mitigate the side effects caused by chemotherapy or even as a supplement to cancer therapy.
Keywords: Cancer therapy; Coupled extraction techniques; Flavonoids; Theaflavin; THP-1